IMF Staff papers, Volume 41 No. 3. (IMF Staff Papers; IMF Staff Papers, 1994)
This paper focuses on the payments system reforms and monetary policy in emerging market economies in Central and Eastern Europe. The reforms in the payments system are viewed as closely interrelated with the development of money and foreign exchange markets and the instruments of monetary policy used by the central banks. The paper shows that although starting from similar origins, there were significant variations in experiences of the countries studied in transforming their payments systems after the start of the reforms toward a market economy, from which certain lessons can be drawn.